Immune response in blood before and after epileptic and psychogenic non-epileptic seizures - Matilda Ahl; Marie K. Taylor; Una Avdic; Anna Lundin; My Andersson; Åsa Amandusson; Eva Kumlien; Maria Compagno Strandberg; Christine T. Ekdahl (Heliyon, 2023)
Inflammatory processes may provoke epileptic seizures and seizures may promote an immune reaction. Hence, the systemic immune reaction is a tempting diagnostic and prognostic marker in epilepsy. We explored the immune response before and after epileptic and psychogenic non-epileptic seizures (PNES). Serum samples collected from patients with videoEEG-verified temporal or frontal lobe epilepsy (TLE or FLE) or TLE + PNES showed increased interleukin-6 (IL-6) levels in between seizures (interictally), compared to controls. Patients with PNES had no increase in IL-6. The IL-6 levels increased transiently even further within hours after a seizure (postictally) in TLE but not in FLE patients. The postictal to interictal ratio of additionally five immune factors were also increased in TLE patients only. We conclude that immune factors have the potential to be future biomarkers for epileptic seizures and that the heterogeneity among different epileptic and non-epileptic seizures may be disclosed in peripheral blood sampling independent of co-morbidities.